Exploring Human-Machine Integration in Modern Manufacturing Environments - Lazuardi, Aditya (Journal of Sustainability Industrial Engineering and Management System, 2023)
This research aims to explore the integration of human-machine collaboration in modern manufacturing environments, particularly focusing on the intersection of advanced technologies such as cyber-physical systems (CPS), artificial intelligence (AI), and collaborative robotics. The primary objective is to examine the role of human operators within these systems and to evaluate the challenges and opportunities that arise when human capabilities are combined with machine precision. A qualitative research methodology, structured as a systematic literature review, was employed to analyze and synthesize relevant academic studies, industry reports, and theoretical frameworks. The research delved into key theoretical models such as the Human-in-the-Loop (HITL) and Human-in-the-Mesh (HIM), which provide foundational perspectives on human involvement in decision-making processes within CPS. Additionally, the study explored cognitive ergonomics, the role of AI, and the psychological impacts of automation on human workers. Key findings include the importance of designing intuitive and adaptive human-machine interfaces to reduce cognitive load and enhance decision-making, as well as addressing the ethical implications of automation on job displacement and worker well-being. Furthermore, the integration of AI and collaborative robotics was found to improve operational efficiency, although human adaptability and continuous training remain crucial for successful implementation. The study concludes with a call for future research on the long-term impact of human-machine integration and the development of self-learning systems that can better collaborate with human operators.